FMECA for Battery Energy Storage System to Load Backup with Integrated Photovoltaic Rooftop in Industry - Papon Ngamprasert; Nawin Rodrueang; Natchapol Ruangsap; Nattachote Rugthaicharoencheep (My University, 2025)
This paper presents FMECA for battery energy storage system to load backup with integrated photovoltaic rooftop in industry. Battery energy storage system requires annual maintenance, which results in this case study. The assessment is done by setting the criteria for performance, environment, safety and financial evaluation by collecting data into Excel program. The results indicate that the financial operation faces a high level of risk, falling within the orange zone. Due to the high maintenance costs, an annual assessment using the FMECA method is required to evaluate the batteries. This approach helps ensure performance, environmental compliance, and safety.
Keywords: Advanced Battery Technologies Research; Power System Reliability and Maintenance; Hybrid Renewable Energy Systems